(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aims to identify the method of joint auditing of the financial statements and identify the principles and principles of the joint audit and the stages that must be carried out to complete the audit process efficiently and effectively. To achieve the objectives of the study, a field study was carried out by designing a questionnaire that was distributed to a sample of the practicing auditors according to the Association of Chartered Accountants in Damascus and then analyzing the results and testing the hypotheses using SPSS. The research has reached the following conclusions: Joint audit affects improved accuracy of risk assessment, particularly agreement on a common audit strategy and decision-making. The joint audit affects the accuracy of the audit risk assessment, particularly the audit planning and the relative importance of the auditor and the auditor’s assessment of the possibility of material errors that will not be prevented or detected by the entity’s internal control. The joint audit affects the accuracy of the risk assessment of the discovery, particularly analytical procedures, in the detection of material misstatement of a particular balance or group of transactions that are not disclosed by the customer’s internal control system and the details of the material misstatement of a particular account or group of transactions. Analytical procedures can be detected. تهدف هذه الدراسة إلى التعرف على أسلوب التدقيق المشترك للبيانات المالية والتعرف على أساسيات ومبادئ التدقيق المشترك والمراحل التي يجب القيام بها لإنجاز عملية التدقيق بالكفاءة و الفعالية اللازمة. ولتحقيق أهداف الدراسة تم القيام بدراسة ميدانية من خلال تصميم استبانة تم توزيعها على عينة من مراجعي الحسابات الممارسيين حسب جمعية المحاسبين القانونين في دمشق ومن ثم تحليل النتائج واختبار فرضيات البحث باستخدام البرنامج الإحصائي SPSS . وتوصل البحث إلى النتائج الأتية: يؤثر التدقيق المشترك في تحسين دقة تقييم المخاطر الكامنة وخاصة الاتفاق على استراتيجية التدقيق واتخاذ القرار بصورة مشتركة على نطاق العمل. يؤثر التدقيق المشترك في تحسين دقة تقييم مخاطر الرقابة وخاصة تخطيط المراجعة والأهمية النسبية وتقدير المدقق باحتمال حدوث أخطاء جوهرية لن يتم منعها أو اكتشافها بواسطة الرقابة الداخلية لدى العميل. يؤثر التدقيق المشترك في تحسين دقة تقييم مخاطر الاكتشاف وخاصة الإجراءات التحليلية في اكتشاف الأخطاء الجوهرية في رصيد معين أو مجموعة من العمليات والتي لم تكتشف من قبل نظام الرقابة الداخلية المُطبَّقة لدى العميل واختبارات التفاصيل في اكتشاف الأخطاء الجوهرية في رصيد حساب معين أو مجموعة من العمليات والتي لم تستطع الإجراءات التحليلية اكتشافها.